2018
DOI: 10.1101/453860
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association between chronic hepatitis C virus infection and myocardial infarction in people living with HIV in the United States

Abstract: Hepatitis C virus (HCV) is common among people living with HIV (PLWH). The potential for extrahepatic manifestations of HCV, including myocardial infarction (MI), is a topic of active research. MI is classified into types, predominantly atheroembolic Type 1 MI (T1MI) and supply-demand mismatch Type 2 MI (T2MI). We examined the association between HCV and MI in the CFAR Network of Integrated Clinical Systems (CNICS), a multi-center clinical cohort of PLWH. MIs were centrally adjudicated and categorized by type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 50 publications
1
2
0
1
Order By: Relevance
“…Our study also found that some traditional risk factors (diabetes, current smoker) were associated with significantly increased odds of hospitalization for an ACS event in our study population. These findings are consistent with the literature [5][6][7][8]10] , suggesting that our study population is sufficiently valid to detect relevant associations between ACS and CVD factors. The literature has mixed findings regarding the association between BMI and CVD, and our study found that BMI was not associated with odds of hospitalization for ACS.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our study also found that some traditional risk factors (diabetes, current smoker) were associated with significantly increased odds of hospitalization for an ACS event in our study population. These findings are consistent with the literature [5][6][7][8]10] , suggesting that our study population is sufficiently valid to detect relevant associations between ACS and CVD factors. The literature has mixed findings regarding the association between BMI and CVD, and our study found that BMI was not associated with odds of hospitalization for ACS.…”
Section: Discussionsupporting
confidence: 92%
“…[6] Finally, a recent study found that chronic HCV infection was associated with increased supply-demand mismatch type 2 AMI but not classical atheroembolic type 1 AMI, highlighting the importance of distinguishing between types of MI. [10] Our study found that infection with HCV was not associated with the odds of hospitalization for an ACS event compared to hospitalization for other conditions. This finding did not support the hypothesis that HCV infection is associated with ACS events among hospitalized patients and was consistent with some studies that showed similar results.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…Данные о роли других заболеваний печени, прежде всего хронического вирусного гепатита В и С, в развитии коронарного атеросклероза и ОКС неоднозначны. Некоторые авторы не выявили повышенного риска развития ИМ у пациентов с HCV-инфекцией [32,33], однако в другом исследовании HCV-инфекция сопровождалась значительным увеличением риска ИМ 2 типа (скорректированное отношение рисков 1,46, 95% ДИ 1,09-1,97), но не ИМ 1 типа [34]. По данным анализа 686 HCV-позитивных пациентов, вирусная инфекция оказалась независимым предиктором ангиографически подтвержденного поражения коронарных артерий (скорректированное ОШ 4,2; 95% ДИ 1,4-13,0) [35].…”
Section: материалы и методыunclassified